Knock Down of Heat Shock Protein 27 (HspB1) Induces Degradation of Several Putative Client Proteins - Gibert, Benjamin; Eckel, Bénédicte; Fasquelle, Lydie; Moulin, Maryline; Bouhallier, Frantz; Gonin, Vincent; Mellier, Gregory; Simon, Stéphanie; Kretz-Remy, Carole; Arrigo, André-Patrick; Diaz-Latoud, Chantal (PLOS ONE, 2012)
Hsp27 belongs to the heat shock protein family and displays chaperone properties in stress conditions by holding unfolded polypeptides, hence avoiding their inclination to aggregate. Hsp27 is often referenced as an anti-cancer therapeutic target, but apart from its well-described ability to interfere with different stresses and apoptotic processes, its role in non-stressed conditions is still not well defined. In the present study we report that three polypeptides (histone deacetylase HDAC6, transcription factor STAT2 and procaspase-3) were degraded in human cancerous cells displaying genetically decreased levels of Hsp27. In addition, these proteins interacted with Hsp27 complexes of different native size. Altogether, these findings suggest that HDAC6, STAT2 and procaspase-3 are client proteins of Hsp27. Hence, in non stressed cancerous cells, the structural organization of Hsp27 appears to be a key parameter in the regulation by this chaperone of the level of specific polypeptides through client-chaperone type of interactions.